Kamus sufi : sejarah, tokoh, ajaran, aliran, seni & budaya - Attarmizi, Yoga Ad. (Yoga Adiana), 1974-; Kalam, M. Yajid, 1975- (Bandung : Kasidah Cinta Studio, Pustaka Kasidah Cinta, 2002)
Dictionary of sufic terms.
Includes bibliographical references (p. [115]-[116]).
Keywords: Sufism -- Dictionaries